2015
DOI: 10.1089/pho.2014.3831
|View full text |Cite
|
Sign up to set email alerts
|

Histological Validation of Cone-Beam Computed Tomography Versus Laser Fluorescence and Conventional Diagnostic Methods for Occlusal Caries Detection

Abstract: Cone beam computed tomography showed better performance than other diagnostic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Some studies [25,30] also show that they improve the accuracy of visual diagnosis. The validity of the visual diagnosis has been compared with DIAGNOdent [4,7,9,12,13,16,18,20,22,[24][25][26] and with VistaProof [4,7,12,30], but few studies have analysed the combination of both methods as complementary to visual diagnosis. Iranzo-Cortés et al [25,30] showed that these possible combinations increase the sensitivity values but decrease the question of specificity and the area under the curve, though not to a significant degree with respect to visual diagnosis only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [25,30] also show that they improve the accuracy of visual diagnosis. The validity of the visual diagnosis has been compared with DIAGNOdent [4,7,9,12,13,16,18,20,22,[24][25][26] and with VistaProof [4,7,12,30], but few studies have analysed the combination of both methods as complementary to visual diagnosis. Iranzo-Cortés et al [25,30] showed that these possible combinations increase the sensitivity values but decrease the question of specificity and the area under the curve, though not to a significant degree with respect to visual diagnosis only.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 27 articles included, 23 used DIAGNOdent [3,4,, studying sensitivity, specificity and AUC in vitro in 16 of them [4,[7][8][9][10][11][13][14][15][16][17]20,[23][24][25][26] while nine were in vivo [3,12,16,18,19,21,22,26,27]; in two cases, however, (Theocharopoulou 2015 [21] and Peycheva 2016 [24]) carried out the study in vivo and in vitro. For VistaProof, 14 articles were reviewed [4,5,7,8,10,12,14,15,19,23,[27][28][29][30], of which 10 were in vitro [4,7,8,10,14,15,23,…”
Section: The Qualitative Analysismentioning
confidence: 99%
“…85 (0.65 Forest plots for meta-analysis and heterogeneity analysis of intra-and inter-examiner reproducibility when ICDAS was used for assessing caries lesion severity. Teo et al [2014] 0.84 (0.61, 1.07) Mitropoulos et al [2010] 0.51 (0.36, 0.66) Braga et al [2010] 0.91 (0.69, 1.13) Parviainen et al [2013] 0.47 (0.02, 0.92) Braga et al [2009b] 0.82 (0.62, 1.02) Achilleos et al [2013] 0.73 (0.28, 1.18) Braga et al [2009a] 0.47 (0.31, 0.63) Ozturk et al [2015] 0.37 (0.17, 0.57) Bussaneli et al [2015] 0.58 (0.17, 0.99) Jallad et al [2015] 0.72 (0.63, 0.81) Study selection was performed independently by 2 reviewers (T.G. and M.M.B.).…”
Section: Systematic Review: the Accuracy Of The Icdas In Detectingmentioning
confidence: 99%
“…So, the intensity of the detected fluorescence indicates the extent of caries [16]. The reliability of DIAGNO dent, in detecting secondary caries under composite restorations, is reported to be similar to digital radiographs [17], however, the Cone beam computed tomography seemed to represent the best accuracy [18]. Near-infrared laser transillumination (NIR-LTI) is another new generation of caries detectors which have shown promising results compared to DIAGNOdent however the researches are not vast enough to make a determined conclusion [19].…”
Section: Materials and Methodologymentioning
confidence: 99%